THE ROLE OF SOCIAL MEDIA IN MARKETING OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) PRODUCT DURING COVID 19 PANDEMIC - Arifah Hidayati; Melvi yansi (Teunuleh Publisher, 2020)
This study aims to explain how the role of social media in marketing MSME products during the Covid 19 pandemic in DKI Jakarta. This research method is qualitative by using phenomenological predictions. The results of this study explain that MSMEs are more dominant in using the TikTok, Instagram, Facebook, and WhatsApp applications in promoting their products because they are easier to implement and can attract more consumer interest through interesting videos and photos. Therefore, social media provides a good prospect for increasing the sales of MSME products in DKI Jakarta which is experiencing the impact of the COVID-19 pandemic. This is because the digital marketing system provides an online buying and selling platform, in order to facilitate the ordering and purchasing process. So that consumers can interact with MSME owners to make transactions directly. The results of this study suggest that MSME have to understand and add insight into the importance of digital marketing strategies to support the sustainability of MSME businesses. Digital marketing is an opportunity that can be developed to achieve maximum business benefits during the COVID-19 pandemic.